2017
DOI: 10.1111/andr.12336
|View full text |Cite
|
Sign up to set email alerts
|

The association of a probiotic with a prebiotic (Flortec, Bracco) to improve the quality/quantity of spermatozoa in infertile patients with idiopathic oligoasthenoteratospermia: a pilot study

Abstract: The hypothesis that the assumption of a probiotic associated with a prebiotic (Flortec, Bracco; one sachet contains: Lactobacillus paracasei B21060 5 × 10 cells + arabinogalctan 1243 mg + oligo-fructosaccharides 700 mg + l-glutamine 500 mg) could improve the quality and quantity of spermatozoa in idiopathic oligoasthenoteratospermia (iAOT) patients to a larger extent than a control substance (starch) was tested. Forty-one patients with no chromosomal aberrations were randomized into two groups: 20 received Flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 17 publications
2
50
0
2
Order By: Relevance
“…The hormonal assessments were carried out in three different laboratories (Bologna, Varese, and Paderno Dugnano) using identical methodology and reference values (rv). The methodology has been described elsewhere (Maretti & Cavallini, ). The FSH rv were 1.5–12.4 mIU/mL; the LH rv were 1.0–10.0 mIU/mL; the T rv were 11–36 nmol/L, and the PRL rv were 80–400 mIU/L.…”
Section: Methodsmentioning
confidence: 99%
“…The hormonal assessments were carried out in three different laboratories (Bologna, Varese, and Paderno Dugnano) using identical methodology and reference values (rv). The methodology has been described elsewhere (Maretti & Cavallini, ). The FSH rv were 1.5–12.4 mIU/mL; the LH rv were 1.0–10.0 mIU/mL; the T rv were 11–36 nmol/L, and the PRL rv were 80–400 mIU/L.…”
Section: Methodsmentioning
confidence: 99%
“…Plummer et al have demonstrated that antimicrobial drugs in the male partners of women with bacterial vaginosis were able to exert beneficial effects reducing disease recurrence [42]. In addition, prebiotics supplementation has shown the ability to ameliorate some semen parameters in both animal models and humans [59][60][61][62]. Dardmeh et al found that Lactobacillus rhamnosus PB01 (DSM 14870) supplementation was able to improve sperm kinematic parameters in mice [59].…”
Section: Diet Supplementation and Semen Microbiotamentioning
confidence: 99%
“…In humans, Valcarce et al assessed that a 6-week supplementation with Lactobacillus and Bifidobacterium improved sperm motility and reduced the percentage of sperm DNA fragmentation in asthenozoospermic males [61]. Maretti et al verified that the daily administration of Lactobacillus paracasei, arabinogalactan, fructo-oligosaccharides, and l-glutamine over a period of 6 months ameliorated sperm count and motility, and reduced the rate of atypical forms, in comparison to the placebo-receiving group [62]. These evidences, if confirmed by larger studies, may pave the way for novel therapeutic strategies for fertility issues.…”
Section: Diet Supplementation and Semen Microbiotamentioning
confidence: 99%
“…Prebiotics and probiotics could also be helpful in men during reproduction. Half-year treatment with orally delivered synbiotic composition of lactic acid bacteria (LAB) and arabinogalactan, FOS and L-glutamine increases the volume of the ejaculate and the quality/quantity of spermatozoa in patients suffering from idiopathic oligoasthenoteratospermia [59]. Likely, such an effect could also be seen in healthy men.…”
Section: Urogenital Tractmentioning
confidence: 99%